L_p -dual mixed affine surface areas - Wan, Xiaoyan; Wang, W. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
Lutwak proposed the notion of L_p-affine surface area according to the Lp-mixed volume. Recently,Wang and He introduced the concept of Lp-dual affine surface area combing with the L_p-dual mixed volume. In the article, we give the concept of L_p-dual mixed affine surface areas associated with the L_p-dual mixed quermassintegrals. Further, some inequalities for the L_p-dual mixed affine surface areas are obtained.